A simulation study of video conferencing system over IEEE 802.11n Wireless LAN - Omar M. Ali; Yazen S. Sheet; Firas S. Alsharbaty (Institute of Advanced Engineering and Science, 2020)
Wireless local area network (WLAN) is the core of the classic wireless communications systems and owns the infrastructure which wide spreads in many regions in the world. IEEE 802.11n is an attractive standard of WLAN and offers a data capacity of the cell. This paper estimates the maximum limits of the IEEE 802.11n standard cell as a term of number of users which are successfully served by the cell in case of video conference application. The results shown that, the cell of 802.11n could serve about 9 users under the service of video conference in case of 20MHz channel bandwidth before congestion occurs while the 40MHz channel could support 18 users.